Effects of Ultrasound Frequency and Tissue Stiffness on the Histotripsy Intrinsic Threshold for Cavitation - Vlaisavljevich, Eli (Ultrasound Med Biol, 2015)
Histotripsy is an ultrasound ablation method that depends on the initiation of a cavitation bubble cloud to fractionate soft tissue. Previous work has demonstrated a cavitation cloud can be formed by a single pulse with one high amplitude negative cycle, when the negative pressure amplitude directly exceeds a pressure threshold intrinsic to the medium. We hypothesize that the intrinsic threshold in water-based tissues is determined by the properties of the water inside the tissue and changes in tissue stiffness or ultrasound frequency will have a minimal impact on the histotripsy intrinsic threshold. To test this hypothesis, the histotripsy intrinsic threshold was investigated both experimentally and theoretically. The probability of cavitation was measured by subjecting tissue phantoms with adjustable mechanical properties and ex vivo tissues to a histotripsy pulse of 1–2 cycles produced by 345 kHz, 500 kHz, 1.5 MHz, and 3 MHz histotripsy transducers. Cavitation was detected and characterized by passive cavitation detection and high-speed photography, from which the probability of cavitation was measured vs. pressure amplitude. The results demonstrated that the intrinsic threshold (the negative pressure at which probability=0.5) is independent of stiffness for Young’s moduli (E) < 1 MPa with only a small increase (~2–3 MPa) in the intrinsic threshold for tendon (E=380 MPa). Additionally, results for all samples showed only a small increase of ~2–3 MPa when the frequency was increased from 345 kHz to 3 MHz. The intrinsic threshold was measured to be between 24.7–30.6 MPa for all samples and frequencies tested in this study. Overall, the results of this study indicate that the intrinsic threshold to initiate a histotripsy bubble cloud is not significantly impacted by tissue stiffness or ultrasound frequency in hundreds of kHz to MHz range.